Power, knowledge and Social Sciences - Germaná Cavero, César (2017)
The inaugural conference addresses central aspects of the problem of power, knowledge and social sciences in a perspective of past, present and future. Reflection that contributes to the necessary debate on the teaching of our disciplines.